برصغیر میں اردو کے ادبی رسائل اور اقبال شناسی کا سفر: A Journey of Urdu Literary Journals and Iqbal Studies in the Subcontinent - Kauser, Dr Yasmeen (Tashkeel e Jadeed, 2026)
Literary magazines and journals have always played an important role in the development and advancement of Urdu language and literature. Because literary magazines act as an effective and active force in the intellectual development and training of the people. The first Urdu-language newspaper, "Jam-e-Jahan Nama", was published in Calcutta on 16 May 1822 in Persian. But soon after, from May 1823, "Jam-e-Jahan Nama" became a Bilingual newspaper, and now an Urdu supplement was also added along with Persian. The foundation stone of Urdu journalism in North India was laid in 1837. Maulvi Muhammad Baqir laid its foundation with "Delhi Urdu Akhbar". Sir Syed Ahmad Khan's brother Syed Muhammad Khan launched the weekly "Sayed-ul-Akhbar" from Delhi in 1837. Master Ram Chandra, a professor of Delhi College, launched the fortnightly newspaper "Fawaid-ul-Nazrin" from Delhi in 1845. (11) Master Ram Chandra published another magazine "Khair khawah-e-Hind" from Delhi in 1847, but in November 1847 the name of this magazine was changed to "Mohab-e-Hind", because another magazine with the same name was being published from Mirzapur. At the beginning of the twentieth century, Allama Iqbal shone as a bright star in the sky of the Urdu language. He started his poetic career with Sheikh Abdul Qadir's magazine "Makhzan". Before that, a few of his ghazals appeared in a few magazines. As Allama Iqbal's popularity started to increase, the editors of other magazines also considered it a great privilege to publish Iqbal's writings. By 1905, Allama Iqbal's popularity among the public had two major platforms. One was the meetings of the Anjuman Himayat-e-Islam and the other was the publication of Iqbal's poetry in "Makhzan". Apart from these, Iqbal's poetry began to be published in other magazines such as "Ma'arif", "Sufi", "Zamana" (Kanpur), "Tamadan" (Delhi), "Zaban", "Vakil", "Urdu-e-Mu'alla", etc.